2022
DOI: 10.1007/s41748-022-00336-8
|View full text |Cite
|
Sign up to set email alerts
|

Pros and Cons of Biochar to Soil Potentially Toxic Element Mobilization and Phytoavailability: Environmental Implications

Abstract: While the potential of biochar (BC) to immobilize potentially toxic elements (PTEs) in contaminated soils has been studied and reviewed, no review has focused on the potential use of BC for enhancing the phytoremediation efficacy of PTE-contaminated soils. Consequently, the overarching purpose in this study is to critically review the effects of BC on the mobilization, phytoextraction, phytostabilization, and bioremediation of PTEs in contaminated soils. Potential mechanisms of the interactions between BC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 167 publications
0
4
0
Order By: Relevance
“…Previous studies have found that peanut-shell-biochar significantly reduced the bioavailable concentration of Cr, Ni, As, Cd, and Pb in the soil as well as their accumulation in Brassica rapa [ 40 ]. The raw materials, pyrolysis temperature, and duration of biochar will affect its adsorption efficiency [ 41 ]. Generally, the stability and pH of biochar pyrolyzed at high temperatures are higher, and the effect is better [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that peanut-shell-biochar significantly reduced the bioavailable concentration of Cr, Ni, As, Cd, and Pb in the soil as well as their accumulation in Brassica rapa [ 40 ]. The raw materials, pyrolysis temperature, and duration of biochar will affect its adsorption efficiency [ 41 ]. Generally, the stability and pH of biochar pyrolyzed at high temperatures are higher, and the effect is better [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the converse effect of the interaction between biochar and PTE mobilization can be strategically utilized. Biochar's potential as a mobilizing agent can be harnessed to enhance phytoremediation efforts for heavy-metalcontaminated soils, particularly PTEs [119].…”
Section: Pros and Cons Of Biocharmentioning
confidence: 99%
“…Thermal conversion of biomass waste into biochar often produces low-cost adsorbents (Ippolito et al 2020;Shaheen et al 2022b). Biochar and other biomass-derived carbon materials are widely used for soil remediation (Hu et al 2020;Papageorgiou et al 2021;Bolster 2021;Shaheen et al 2023) and water purification (Heo et al 2019;Jie et al 2019;Huang et al 2019;Peng et al 2022). However, conventional carbon materials, including biochar, have limited sorption ability to anionic pollutants because of the high negative charges on their surfaces under conditions of non-optimal pH.…”
Section: Introductionmentioning
confidence: 99%